Kesiapan Kerja Setelah Melaksanakan Praktek Kerja Industri Siswa Kelas XII SMK Negeri 2 Solok - Myori, Dwiprima Elvanny; Priyatno, Aulia (Lembaga Yasin AlSys, 2024)
This research aims to determine the impact of industrial work practices on the readiness for work among 12th-grade students in electrical installation engineering at SMK Negeri 2 Solok. This study falls under quantitative research, with the research subjects being 26 12th-grade students in electrical installation engineering at SMK Negeri 2 Solok. Data collection was done through questionnaires and documentation. The questionnaire was used to measure variables related to industrial work practices, student readiness, and the location of industrial work practice. Data analysis was conducted using data analysis tests for normality, homogeneity, and the F-test. The questionnaire results indicate an influence on the readiness for work among 12th-grade students in electrical installation engineering, with an average questionnaire score of 178, a maximum score of 218, a minimum score of 117, and a standard deviation of 23.681. The normality test yielded a sig(2-tailed) value of 0.894 > 0.05, the homogeneity test had a sig value of 0.758 > 0.05, and the F-test had a sig value of 0.013 < 0.05. Based on the data analysis results, it can be concluded that there is an impact after conducting industrial work practice on the readiness for work among 12th-grade students in electrical installation engineering.